Enhanching Listening Skills By Using Digital-Assisted Platform - Moh. Raul Figo; Aminah Suriaman; Muhammad Arid; Anjar Kusuma Dewi (Universitas Cokroaminoto Palopo, 2025)
This research aimed to determine whether the use of a digital-assisted platform could enhance the listening comprehension skills of eleventh-grade students at SMA Negeri 4 Sigi. The research used a quantitative method, adopting a quasi-experimental design. Data collection involved administering pre-tests and post-tests, with participants split into two distinct groups: an experimental group and a control group. The primary research instrument was a listening comprehension test. The researcher compared the students’ listening abilities before and after the experimental group received treatment using the digital-assisted platform. The results showed that the post-test t-count value (1.723) was greater than the t-table value (1.670) at a 0.05 significance level with 64 degrees of freedom. Based on this analysis, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. In other words, the findings indicate a statistically significant difference in post-test results between the experimental group and the control group. This suggests that the use of digital-assisted platforms has a positive and significant impact on students’ listening skills.